Toxicology international - Society of Toxicology (India) (Mumbai, India : Medknow Publications Pvt, Ltd., 2003)
The Journal is concerned all aspects of toxicology of drugs, chemicals including pesticides, indigenous drugs, epidemiological aspects covering human beings, animals, plants, environmental sciences, etc. The journal publishes research, review and general articles besides opinions, comments, news-highlights and letters to editor.
Official journal of the Society of Toxicology.
Description based on: Vol. 17(1) (Jan./June 2010); title from issue table of contents (PubMed Central, viewed Jan. 31, 2011).
Latest issue consulted: Vol. 18(1) (Jan./June 2011) (Galegroup, viewed Feb. 7, 2011).
Keywords: Toxicology -- Periodicals; Hazardous Substances -- toxicity -- Periodicals; Toxicology -- Periodicals; Toxicology; Electronic journals